Allergic asthma manifestations in human and seropositivity to Toxocara, a soil-transmitted helminth of carnivores: A case-control study and scoping review of the literature - Bazargan, Nasrin; Lari, Azadeh Nasri; Borhani, Mehdi; Fasihi Harandi, Majid (Frontiers in Medicine, 2022)
Asthma is a common respiratory disease of human. Helminth parasites, including Toxocara species have been implicated as predisposing factors of asthma. However various studies present different findings on asthma-Toxocara association. Herein, we investigated the association of asthma manifestations with Toxocara seropositivity in a case-control setting on 248 participants (147 females and 101 males), including124 healthy individuals as the control group and 124 known asthmatic patients based on the medical records of asthma clinics of Kerman University of Medical Sciences. Consequently, we have presented a scoping review on all previous studies carried out on this topic, summarizing current findings and existing knowledge on this issue. Thirty-one (12.5%) out of 248 participants were Toxocara seropositive, of which 19 (15.3%) were in the patient group and 12 (9.7%) in the control group. A significant relationship was found between the asthma severity and age in Toxocara seropositive individuals (P<0.04). We found no significant relationship between asthma and Toxocara seropositivity. We identified 7724 related records in three major scientific databases, NCBI PubMed, Scopus and Scholar Google. The review of the literature showed that 80 studies have been published on asthma-Toxocara relationship with contradictory findings. More than half of the studies were performed in only four countries, i.e Brazil, the Netherlands, the United States, and Iran. The study population in 70% of the articles were children and few studies have investigated asthma-Toxocara association in adults. The most common study designs for investigating the association of asthma and Toxocara seropositivity were cross‐sectional (35.0%), case-control (27.5%) and animal experiments (12.5%). This study found no significant relationship of asthma manifestations and toxocariasis in a case-control setting. However scoping review of current literature suggests that further experimental and field studies are required to elucidate the nature of asthma-Toxocara interaction in human.